Solitary diffuse neurofibroma of buccal mucosa - Rekha Bhaskar Chaudhari (Wolters Kluwer Medknow Publications, 2017)
Neurofibroma (NF) is a benign peripheral nerve sheath tumor, arising from the mixture of Schwann cells and perineural fibroblasts. Diffuse NF (DNF) is an uncommon but distinct histological variant of NF. It typically involves skin and subcutaneous tissues, occurring primarily in children and young adults. DNF is seen either as a sporadic (solitary) lesion or as part of neurofibromatosis, usually type 1-NF1 (von Recklinghausen's disease of skin). Involvement of oral cavity is rare with isolated reports in the literature. Clinically, it appears as pedunculated or sessile nodular mass, exhibiting slow growth and mostly without pain. Histologically it differs from the conventional NF in that it has a very uniform matrix of fine-fibrillary collagen. Sheets or cords of neoplastic Schwann cells in the matrix are less elongated and has short fusiform or round contour. A characteristic feature is the presence of clusters of laminated Wagner-Meissner-like bodies, scattered throughout tumor mass, which distinguishes DNF from NF. A case of solitary DNF of buccal mucosa in a 23-year-old female patient is presented.